David Busch's Nikon Z6 guide to digital photography - Busch, David D. (Rocky Nook, 2019)
David Busch's Nikon Z6 Guide to Digital Photography is your all-in-one comprehensive resource and reference for the exciting and affordable Nikon Z6 compact mirrorless camera. This ground-breaking enthusiast camera is built around a 24.5 megapixel sensor, that offers excellent image quality and ISO speeds from ISO 100-51200. The Z6 can be fitted with any of the new ultra-sharp S-series, Z-mount lenses, or mount a full line of Nikon's existing F-mount lenses, with the optional FTZ adapter. Five-axis in-body image stabilization provides up to five stops of anti-shake performance so you can hand-hold the camera at slower shutter speeds. With 273 phase-detect AF focus points, covering 90 percent of the frame, and the next-generation EXPEED 6 processing chip, the Z6 can shoot sports and action at up to 12 frames per second, with lightning fast focus. The Z6 can capture both 4K and Full HD movies, too. With this book in hand, you'll master all the camera's impressive features, and fine tune your camera skills as develop your creativity taking great photographs with your new Z6. Filled with detailed how-to steps and full-color illustrations, David Busch's Nikon Z6 Guide to Digital Photography covers all the camera's capabilities in depth, from taking your first photos through advanced details of setup, exposure, lens selection, lighting, and more, and relates each feature to specific photographic techniques and situations. Also included is the handy visual guide to the Z6, with close-up photos and descriptions of the camera's essential features and controls. Learn when to use each option and, more importantly, when not to use them, by following the author's recommended settings for every menu entry. With best-selling photographer and mentor David Busch as your guide, you'll quickly have full creative mastery of your camera's capabilities, whether you're shooting on the job, as an advanced enthusiast, or are just out for fun. Start building your knowledge and confidence, while bringing your vision to light with the Nikon Z6 today.